An in vitro Survey on the Effect of Six Commercial Brands of Phosphoric Acid on the Micro-shear Bond Strength of Composite Resin to Enamel - Faeze Jamali Zavare; Mahsa Sheikholeslamian; Saber Kazemi; Amir Ghasemi; Narges Panahandeh; Mina Yazdizadeh; Elham Zanguei (Journal of Dentistry)
Statement of the Problem: One of the most important factors in the clinical longevity of composite resin restorations is proper adhesion, which is achieved using phosphoric acid. Different phosphoric acid products might affect the micro-shear bond strength of composite resin to enamel.Purpose: The present study aimed to evaluate the micro-shear bond strength of composite resin to sound enamel using six different brands of acid-etch agents.Materials and Method: The present in vitro study was carried out on 72 extracted sound human (mandibular and maxillary) first premolar teeth. The teeth crowns were divided into two equal parts with a mesiodistal cut and randomly assigned to six groups in terms of the acid etchant brand: Ultra-etch, SDI, Morvabon, FGM, Nik Darman, and Experimental. The bonding procedure was carried out using the Margin Bond enamel adhesive. Tygon tubes (1×0.7 mm) containing composite resin were bonded to each enamel surface. After 24 hours of storage in distilled water, each sample underwent a shearing force with a crosshead speed of 0.5 mm/min. The morphologic changes were evaluated using scanning electron microscopy. The data were analyzed with SPSS using one-way ANOVA and Tukey test (p< 0.05).Results: One-way ANOVA showed that micro-shear bond strength in different etchant agents have significant differences (p< 0.001). The highest and lowest composite resin micro-shear bond strengths belonged to Ultradent and SDI brands, respectively. The enamel surfaces in the SDI group revealed residual debris after dissolution.Conclusion: Preparation of the enamel surface with different phosphoric acid products might affect the micro-shear bond strength and enamel surface morphology differently. Further clinical studies are suggested to evaluate the effect of different types and concentrations of acid etching agents on the enamel and dentin bonds.